A Method to Quantify Material Parameter Uncertainties Resulting from Microstructure Variation based on Artificial Microstructures. Issue 1 (17th December 2018) - Miska, Niklas; Balzani, Daniel
Abstract: The macroscopic behavior of many materials is dependent from their microstructure morphology. As the morphology is often random, the macroscopic response of the material is uncertain. In this paper we propose a method to capture the statistics of the variability of the morphology of the real material, transfer this variability to artificial microstructures and perform virtual tests to quantify the uncertainty of the resulting macroscopic response.